Melanoma cell lysosome secretory burst neutralizes the CTL-mediated cytotoxicity at the lytic synapse - Khazen, Roxana (Nat Commun, 2016)
Human melanoma cells express various tumour antigens that are recognized by CD8(+) cytotoxic T lymphocytes (CTLs) and elicit tumour-specific responses in vivo. However, natural and therapeutically enhanced CTL responses in melanoma patients are of limited efficacy. The mechanisms underlying CTL effector phase failure when facing melanomas are still largely elusive. Here we show that, on conjugation with CTL, human melanoma cells undergo an active late endosome/lysosome trafficking, which is intensified at the lytic synapse and is paralleled by cathepsin-mediated perforin degradation and deficient granzyme B penetration. Abortion of SNAP-23-dependent lysosomal trafficking, pH perturbation or impairment of lysosomal proteolytic activity restores susceptibility to CTL attack. Inside the arsenal of melanoma cell strategies to escape immune surveillance, we identify a self-defence mechanism based on exacerbated lysosome secretion and perforin degradation at the lytic synapse. Interfering with this synaptic self-defence mechanism might be useful in potentiating CTL-mediated therapies in melanoma patients.